Laparoscopic Surgery for Colorectal Endometriosis and its Impact upon Fertility: An Updated Australian Series of 307 Cases. Issue 3 (July 2017) - Wills, Hannah; Tsaltas, Jim; Cooper, Michael J.W.; Reid, Geoffrey D.; Morgan, Matthew; Woods, Rod; Barel, Oshri
Introduction: Colorectal involvement occurs in up to 12% of cases of endometriosis. Various surgical options for its management have been described, including segmental resection and disc excision, with debate surrounding indications for surgery and the impact of such procedures. The current study aimed to describe the experiences of three Australian gynaecologists regarding laparoscopic bowel surgery for colorectal endometriosis. Methods: The records of three gynaecological surgeons were analysed for patients who underwent surgical removal of colorectal endometriosis by way of appendicectomy, bowel disc excision and/or segmental resection, between 1999 and 2012. Results: A total of 307 patients were identified. Sixteen (5.2%) underwent appendicectomy, 146 (47.6%) underwent disc excision, 126 (41.0%) underwent segmental resection and 19 (6.2%) underwent simultaneous procedures. The majority of procedures were performed laparoscopically (265 of 307; 86.3%). Nineteen procedures (6.2%) were planned laparotomies due to the known extent of disease. Twenty-three procedures were converted from laparoscopy to laparotomy (conversion rate of 7.5%). Complications occurred in 35 of the 307 cases (11.4%). Sixty-seven women amongst the 122 wishing to conceive post-operatively achieved at least one pregnancy (pregnancy rate of 54.9%). Of the 84 pregnancies achieved amongst the 67 women who conceived, 49 (58.3%) were achieved through assisted reproductive technologies, and 31 pregnancies (36.9%) were conceived spontaneously. This information was unavailable for 4 pregnancies (4.8%). Conclusions: The current series demonstrates that laparoscopic surgery for severe disease is feasible in specialised centres. Furthermore, such surgery may have a positive impact upon post-operative fertility.